Catalytic reduction of 4-Nitrophenol using magnetic biostabilised silver nanoparticles - Salsadhila Jusoh, 1994-; Mustafa Shamsuddin; Fakulti Sains (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Sains (Kimia) - Universiti Teknologi Malaysia, 2017